Preparation method of phosphorus removal polymer gel

By using modified nano-hydroxyapatite and nano-ferrous tetraoxide combined with sodium alginate and amide compounds, the problem of low removal rate and difficulty in separation of existing phosphorus removal technology in high concentration phosphorus-containing wastewater is solved, and efficient removal and separation of phosphate is achieved, with good stability and environmental protection.

CN119633775AActive Publication Date: 2025-03-18YUNNAN UNIV

Patent Information

Application Number
CN202411893616.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing phosphorus removal technology has low removal rate in high-concentration phosphorus-containing wastewater, and it is difficult to achieve efficient separation and recycling, which can easily cause waste of resources and secondary pollution.

Method used

Nanohydroxyapatite and nanoferrous tetroxide are used as main components, and through ultrasonic dispersion and modification treatment, sodium alginate and amide compounds are combined to form a polymer gel. The gel achieves efficient adsorption and separation of phosphate through electrostatic attraction, chemical bonding and cross-linking reactions.

Benefits of technology

It realizes rapid and efficient removal of phosphate in water, and efficient separation and recycling after adsorption is completed, avoiding resource waste and secondary pollution, and the gel material has good stability and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201197680000111
    Figure BDA0005201197680000111
  • Figure BDA0005201197680000121
    Figure BDA0005201197680000121
Patent Text Reader

Abstract

The invention relates to the technical field of water pollution treatment, and particularly discloses a preparation method of phosphorus removal polymer gel, which comprises the following steps: reacting sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl) acrylamide, acrylamide and a cross-linking agent to obtain the phosphorus removal polymer gel; the nano-hydroxyapatite and the nano-ferroferric oxide in the polymer gel have rich micropores, specific surface area and adsorption sites, the sodium alginate can form a three-dimensional network structure, provide supporting and fixing effects and increase the specific surface area and the adsorption sites of the material, and through the synergistic effect of adsorption and precipitation of the polymer gel, the specific surface area and the adsorption sites of the material are increased. The method has the advantages that phosphate can be efficiently removed, nano ferroferric oxide has superparamagnetism, rapid separation and effective recovery can be realized through a magnetic separation method, the recovery process is simplified, the recovery cost is reduced, secondary pollution is reduced, and the method is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water pollution control, in particular to a method for preparing a phosphorus removal polymer gel. Background Art

[0002] Phosphorus in nature is widely distributed in the biosphere in the form of phosphates and is one of the elements necessary for the life activities of humans, animals and plants. Humans' unrestrained production and living behaviors have destroyed the normal phosphorus cycle in nature. Every year, excessive phosphorus enters the water environment through sewage discharge and agricultural runoff, causing eutrophication of water bodies, causing a large number of algae to reproduce in the water, and a sharp decrease in dissolved oxygen in the water, which seriously threatens the survival of aquatic organisms and human health.

[0003] Phosphorus in water bodies mainly exists in three forms: organic phosphorus, orthophosphate and polymeric phosphorus, of which orthophosphate and polymeric phosphorus account for the majority. Traditional phosphorus removal technologies include chemical precipitation, biological methods, electrolysis, etc., but these technologies will cause new polymers to appear in the water during application, thus causing secondary pollution. Adsorption phosphorus removal has the characteristics of simple operation, recyclability, and no secondary pollution, and has become the research focus of phosphorus water pollution control.

[0004] Chinese patent application CN102614854A discloses a method for preparing a dephosphorization iron-carrying activated carbon adsorbent, wherein the powdered activated carbon is soaked in hydrochloric acid and then washed with water, impregnated in a strong oxidizing acid solution, mixed with an inorganic iron salt solution, and dried to obtain an efficient dephosphorization activated carbon adsorbent rich in iron oxide compounds, wherein the dephosphorization iron-carrying activated carbon adsorbent has mild preparation conditions, is easy to implement, and has strong operability, but has a low phosphorus removal rate in high-concentration phosphorus-containing wastewater. Chinese patent application CN104785177A discloses a method for preparing alginate-graphene composite double network gel balls, wherein a graphene oxide aqueous solution and alginate are stirred to form a uniform mixed solution, which is then dropped into a divalent salt ion solution, then added to an aqueous solution containing a reducing agent, and heated in a water bath to obtain alginate-graphene composite double network gel balls, wherein the alginate-graphene composite double network gel balls have a simple process, are easy to promote, have a large specific surface area, and have strong adsorption, but have a single separation means, cannot achieve efficient separation after adsorption, and are prone to waste of resources.

[0005] Therefore, it is of great significance to develop an efficient, stable and environmentally friendly phosphorus removal material. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a phosphorus removal polymer gel. The prepared polymer gel can quickly and efficiently remove phosphate from water bodies, and can also achieve efficient separation and recovery after adsorption.

[0008] (II) Technical solution

[0009] In order to achieve the above object, the present invention discloses a method for preparing a phosphorus removal polymer gel, comprising the following steps:

[0010] S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, after uniform ultrasonic dispersion, adding 2-butene-1-ylsuccinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, stirring and mixing, reacting, after the reaction is completed, filtering, washing with 75% ethanol solution, and vacuum drying at 60° C. for 12 h to obtain modified hydroxyapatite;

[0011] S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, adding γ-aminopropyltriethoxysilane after uniform dispersion, stirring and mixing, reacting, and washing with anhydrous ethanol after the reaction is completed, and vacuum drying at 60° C. for 12 h to obtain aminoferroferric oxide;

[0012] S3, mixing toluene, modified hydroxyapatite, amino ferric oxide and triethylamine evenly, heating, reacting, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60° C. for 24 h to obtain modified ferric oxide-hydroxyapatite;

[0013] S4. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water, add crosslinking agent, initiator and catalyst in a nitrogen atmosphere, heat up, stir and mix to react, and after the reaction, wash with anhydrous ethanol and deionized water, freeze-dry to obtain a dephosphorus polymer gel.

[0014] Preferably, the mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-ylsuccinic anhydride, 4-dimethylaminopyridine and sodium hydroxide in S1 is 100:2500-3000:52-60:2-3:1-1.5.

[0015] Preferably, the reaction temperature in S1 is 85-95° C., and the reaction time is 6-9 h.

[0016] Preferably, the mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane in S2 is 100:1800-2100:65-75.

[0017] Preferably, the reaction temperature in S2 is 25-35° C., and the reaction time is 2-4 h.

[0018] Preferably, the mass ratio of toluene, modified hydroxyapatite, aminoferric oxide and triethylamine in S3 is 4500-6000:100:20-30:1-2.

[0019] Preferably, the reaction temperature in S3 is 80-90° C., and the reaction time is 12-14 h.

[0020] Preferably, the mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, crosslinking agent, initiator and catalyst in S4 is 100:15-20:75-105:240-320:1200-1500:28-40:1-3:2-3.5.

[0021] Preferably, the reaction temperature in S4 is 55-65° C., and the reaction time is 5-8 h.

[0022] Preferably, in S4, the crosslinking agent is methylenebisacrylamide, the initiator is ammonium persulfate, and the catalyst is tetramethylethylenediamine.

[0023] (III) Beneficial technical effects

[0024] In the present invention, 2-butene-1-yl succinic anhydride is used to modify nano hydroxyapatite, the anhydride on the 2-butene-1-yl succinic anhydride reacts with the hydroxyl on the nano hydroxyapatite, and an agent alkenyl and carboxyl groups are introduced on the nano hydroxyapatite to obtain modified hydroxyapatite. γ-aminopropyl triethoxysilane is used to modify nano ferroferric oxide, and amino groups are introduced on the nano ferroferric oxide to obtain amino ferroferric oxide. The carboxyl groups on the modified hydroxyapatite and the amino groups on the amino ferroferric oxide undergo an amidation reaction to obtain modified ferroferric oxide-hydroxyapatite. Sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl) acrylamide and acrylamide are polymerized and cross-linked under the action of a cross-linking agent and an initiator to obtain a phosphorus removal polymer gel.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) In the present invention, nanometer hydroxyapatite is an effective phosphorus adsorption material. The calcium ions on the surface can combine with the phosphate ions in the water to form a poorly soluble calcium phosphate precipitation. At the same time, the hydroxyl groups on the surface of hydroxyapatite can exchange with the phosphate ions in the water. The phosphate ions are adsorbed on the material surface by electrostatic adsorption and chemical bonding, so as to achieve the purpose of removing phosphorus in the water body. The surface of nanometer ferroferric oxide is positively charged, and electrostatic attraction can occur with the negatively charged phosphate ions, which are adsorbed on the material surface. Further, the iron ions on the surface of nanometer ferroferric oxide can exchange with the phosphate ions to form a stable complex, thereby achieving the removal of phosphorus. Modified hydroxyapatite and amino ferroferric oxide are reacted to obtain modified ferroferric oxide-hydroxyapatite, which is then polymerized and cross-linked with other raw materials to prepare a polymer gel, which effectively avoids the agglomeration of nanometer hydroxyapatite and nanometer ferroferric oxide, and can be evenly dispersed in the gel matrix to improve the comprehensive performance of the gel.

[0027] (2) In the present invention, sodium alginate is used as the skeleton structure of the polymer gel, and is combined with nano-hydroxyapatite, nano-ferroferric oxide, N-(hydroxymethyl) acrylamide, and acrylamide to form a polymer gel with excellent phosphorus removal performance. Sodium alginate can form a three-dimensional network structure, provide support and fixation for the polymer gel material, and increase the specific surface area and adsorption sites of the material at the same time. The hydroxyl groups in sodium alginate can undergo ligand exchange reaction with phosphate ions, and adsorb the phosphate ions on the surface of the material or in the micropores. The polyacrylamide introduced into the polymer gel has a good flocculation effect, and mainly plays a role in improving and strengthening solid-liquid separation in the phosphorus removal process. The introduced N-(hydroxymethyl) acrylamide is reactive, and the hydroxymethyl group can react with phosphorus, which is helpful for the removal of phosphorus. Its cross-linking ability enables it to form a network structure on the surface of the material, enhance the stability and performance of the material, and greatly enhance the mechanical properties. The various components in the polymer gel can quickly and efficiently remove phosphorus in the water body through synergistic action, adsorption and chemical bonding.

[0028] (3) The modified hydroxyapatite and amino ferric oxide in the present invention have abundant micropores and specific surface area, and have abundant adsorption sites. Phosphate molecules are adsorbed on the surface or micropores of the gel material through physical forces such as van der Waals force, thereby reducing the phosphorus content in the water. The mesh structure in the polymer gel can capture and sweep suspended particles and colloidal substances in the water, including phosphate precipitates, etc., thereby accelerating their sedimentation and removal. The polymer chains in the polymer gel can play a bridging role, connecting multiple phosphate molecules or precipitate particles together to form larger aggregates, thereby accelerating the removal of phosphate from water. The amide bonds introduced during the reaction process can improve the hydrophilicity, surface charge and other properties of the material, thereby enhancing its adsorption capacity for phosphorus, increasing the material's adsorption capacity for phosphorus, and improving the adsorption efficiency. The gel material has good stability and can maintain its phosphorus removal performance under different environmental conditions. The raw materials used in the preparation process are environmentally friendly substances, which are harmless to the environment and conform to the development trend of green chemistry. Through the synergistic effect of adsorption and precipitation, the polymer gel can achieve efficient removal of phosphate. Furthermore, nano-ferroferric oxide has superparamagnetism, which enables it to be quickly separated and effectively recovered by magnetic separation, simplifying the recovery process, reducing recovery costs, achieving recycling, and reducing the generation of secondary pollution. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0032] S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, after uniform ultrasonic dispersion, adding 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, wherein the mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide is 100:2500:52:2:1, stirring and mixing, reacting at 85°C for 9 hours, after the reaction is completed, filtering, washing with 75% ethanol solution, and vacuum drying at 60°C for 12 hours to obtain modified hydroxyapatite;

[0033] S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane is 100:1800:65, stirring and mixing, reacting at 25°C for 4 hours, after the reaction is completed, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain amino-ferroferric oxide;

[0034] S3, mixing toluene, modified hydroxyapatite, amino ferric oxide and triethylamine in a mass ratio of 4500:100:20:1, heating and reacting at a temperature of 80°C for 14 hours. After the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 24 hours to obtain modified ferric oxide-hydroxyapatite;

[0035] S4. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent methylenebisacrylamide, an initiator ammonium persulfate and a catalyst tetramethylethylenediamine, wherein the mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:15:75:240:1200:28:1:2. Heat up, stir and mix, react at 55°C for 8 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0036] Example 2

[0037] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0038] S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, uniform ultrasonic dispersion, adding 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, wherein the mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide is 100:2800:80:2.5:1.2, stirring and mixing, reacting at 90°C for 8 hours, after the reaction is completed, filtering, washing with 75% ethanol solution, and vacuum drying at 60°C for 12 hours to obtain modified hydroxyapatite;

[0039] S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane is 100:2000:72, stirring and mixing, reacting at 30° C. for 3 hours, after the reaction is completed, washing with anhydrous ethanol, and vacuum drying at 60° C. for 12 hours to obtain amination of ferroferric oxide;

[0040] S3, toluene, modified hydroxyapatite, amino ferric oxide and triethylamine in a mass ratio of 5000:100:24:1.4 were mixed evenly, the temperature was raised, and the reaction occurred at a temperature of 85°C and a reaction time of 13 hours. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 24 hours to obtain modified ferric oxide-hydroxyapatite;

[0041] S4. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:16:90:280:1350:32:1.8:2.5. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0042] Example 3

[0043] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0044] S1. Mix toluene, modified hydroxyapatite, amino ferric oxide and triethylamine in a mass ratio of 5000:100:28:1.6, heat up, and react at a temperature of 85°C for 13 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60°C for 24 hours to obtain modified ferric oxide-hydroxyapatite;

[0045] S2. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:16:90:280:1350:32:1.8:2.5. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0046] The preparation methods of the modified hydroxyapatite and amination of ferrosoferric oxide are the same as those of the modified hydroxyapatite and amination of ferrosoferric oxide in Example 2.

[0047] Example 4

[0048] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0049] S1. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:18:100:300:1450:38:2.5:3. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0050] The preparation method of the modified ferroferric oxide-hydroxyapatite is the same as the preparation method of the modified ferroferric oxide-hydroxyapatite in Example 3.

[0051] Example 5

[0052] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0053] S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, uniform ultrasonic dispersion, adding 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, wherein the mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide is 100:3000:60:3:1.5, stirring and mixing, reacting at 95°C for 6 hours, after the reaction is completed, filtering, washing with 75% ethanol solution, and vacuum drying at 60°C for 12 hours to obtain modified hydroxyapatite;

[0054] S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane is 100:2100:75, stirring and mixing, reacting at 35°C for 2h, after the reaction is completed, washing with anhydrous ethanol, and vacuum drying at 60°C for 12h to obtain amino-ferroferric oxide;

[0055] S3, mixing toluene, modified hydroxyapatite, amino ferric oxide and triethylamine in a mass ratio of 6000:100:30:2, heating and reacting at 90°C for 12 hours. After the reaction, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 24 hours to obtain modified ferric oxide-hydroxyapatite;

[0056] S4. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:20:105:320:1500:40:3:3.5. Heat up, stir and mix, react at 65°C for 5 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0057] Comparative Example 1

[0058] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0059] S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, uniform ultrasonic dispersion, adding 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, wherein the mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-yl succinic anhydride, 4-dimethylaminopyridine and sodium hydroxide is 100:2800:80:2.5:1.2, stirring and mixing, reacting at 90°C for 8 hours, after the reaction is completed, filtering, washing with 75% ethanol solution, and vacuum drying at 60°C for 12 hours to obtain modified hydroxyapatite;

[0060] S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane is 100:2000:72, stirring and mixing, reacting at 30° C. for 3 hours, after the reaction is completed, washing with anhydrous ethanol, and vacuum drying at 60° C. for 12 hours to obtain amination of ferroferric oxide;

[0061] S3. Evenly mix sodium alginate, modified hydroxyapatite, amino ferric oxide, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a crosslinking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, modified hydroxyapatite, amino ferric oxide, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a crosslinking agent, an initiator and a catalyst is 100:14:4:100:300:1450:38:2.5:3. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0062] Comparative Example 2

[0063] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0064] S1. Evenly mix sodium alginate, nano-hydroxyapatite, nano-ferrous oxide, N-(hydroxymethyl)acrylamide, acrylamide and deionized water. In a nitrogen atmosphere, add a cross-linking agent, methylenebisacrylamide, an initiator, ammonium persulfate and a catalyst, tetramethylethylenediamine. The mass ratio of sodium alginate, nano-hydroxyapatite, nano-ferrous oxide, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, a cross-linking agent, an initiator and a catalyst is 100:14:4:100:300:1450:38:2.5:3. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0065] Comparative Example 3

[0066] A method for preparing a phosphorus removal polymer gel comprises the following steps:

[0067] S1. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite and deionized water in a nitrogen atmosphere, wherein the mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite and deionized water is 100:18:1450. Heat up, stir and mix, react at 60°C for 6 hours. After the reaction, wash with anhydrous ethanol and deionized water, and freeze-dry to obtain a dephosphorus polymer gel.

[0068] The preparation method of the modified ferroferric oxide-hydroxyapatite is the same as the preparation method of the modified ferroferric oxide-hydroxyapatite in Example 3.

[0069] The nano-iron tetroxide described in the embodiments and comparative examples of the present invention is prepared by the following steps: 3 6H 2 O and FeCl 2 ·4H 2 O was added to the reactor, and then deionized water and hydrochloric acid were added. In a nitrogen atmosphere, the mixture was stirred and mixed, and sodium hydroxide solution was added. The mass ratio of sodium hydroxide to deionized water in the sodium hydroxide solution was 3:100, in which FeCl 3 6H 2 O, FeCl 2 ·4H 2 The mass ratio of O, deionized water, hydrochloric acid and sodium hydroxide solution is 4.8:2:100:2:103, and the mixture is stirred and reacted. After the reaction, an external magnetic field is used for separation, and the mixture is washed with deionized water and anhydrous ethanol, and vacuum dried at 60°C for 12 hours to obtain nano-iron tetroxide.

[0070] The nano-hydroxyapatite in the examples and comparative examples of the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the sodium alginate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; and other undisclosed raw materials and reagents were commercially available.

[0071] The phosphorus removal polymer gels in Examples 1-5 and Comparative Examples 1-3 were used as samples to perform performance tests, and the relevant performance tests are as follows:

[0072] (1) Test for phosphorus removal: Prepare a potassium dihydrogen phosphate solution with a concentration of 10 mg / L and conduct an adsorption experiment. Take 100 mL of potassium dihydrogen phosphate solution in a conical flask, add 0.1 g of phosphorus removal polymer gel, stir and mix, put the conical flask in a constant temperature oscillator for oscillation and adsorption, and measure the residual phosphorus concentration in the conical flask at 1 h, 2 h, and 4 h, respectively. Q = (C0 -C 1 ) / C 0 ×100%, where Q is the phosphorus removal rate, C 0 is the initial concentration of inorganic phosphorus in the solution, C 1 In order to determine the inorganic phosphorus concentration in the solution after adsorption, the national standard method was used to test the inorganic phosphorus content in the solution using ammonium molybdate visible spectrophotometry, and the Q value was calculated. Each group was tested three times and the average value was taken. The test results are shown in Table 1:

[0073] Table 1

[0074]

[0075] (2) Swelling performance test: The phosphorus removal polymer gel was made into a cylindrical specimen with a diameter of 1.0 cm and a height of 1 mm, dried to constant weight, and immersed in a hydrochloric acid solution with a pH of 1 and a PBS solution with a pH of 7 for 6 h. The specimen was taken out and weighed every 2 h to calculate the swelling rate Q. W , Q W =(W 1 -W 0 ) / W 0 , where W 0 is the dry weight of the sample, W 1 is the weight of the sample after immersion. Each group was tested three times and the average value was taken. The test results are shown in Table 2:

[0076] Table 2

[0077]

[0078] According to the test results of Table 1 and Table 2, it can be seen that the polymer gel corresponding to Examples 1-5 has excellent phosphorus removal rate and stable swelling rate, and can efficiently remove phosphorus in water. The polymer gel can maintain a relatively constant volume and morphology during the adsorption process, which is conducive to full contact and adsorption with phosphate, and can quickly reach a stable balance, while reducing the loss of gel during the adsorption process, and improving adsorption efficiency. And under different pH conditions, the polymer gel has a stable swelling rate, is not easy to undergo significant volume changes due to environmental changes, has good stability, absorbs more water in neutral solutions, and absorbs less water in acidic solutions. In Comparative Example 1, modified hydroxyapatite and amino ferric oxide are used instead of modified ferric oxide-hydroxyapatite, and the dispersibility of the polymer gel deteriorates, the swelling rate increases, the stability decreases, and the time to reach equilibrium stability increases, the removal rate of phosphorus is reduced, and the adsorption equilibrium takes a long time. In Comparative Example 2, nano-hydroxyapatite and nano-ferric oxide are not modified, and the comprehensive performance is greatly reduced, the swelling rate is greatly improved, and the removal rate of phosphorus is greatly reduced. In Comparative Example 3, sodium alginate, modified ferroferric oxide-hydroxyapatite and deionized water were directly mixed to obtain a phosphorus removal polymer gel, which did not undergo cross-linking, greatly increased the swelling rate and had a low phosphorus removal rate.

[0079] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a phosphorus removal polymer gel, characterized in that: The steps include: S1. Ultrasonic dispersion of nano-hydroxyapatite in N,N-dimethylformamide, after uniform ultrasonic dispersion, adding 2-butene-1-ylsuccinic anhydride, 4-dimethylaminopyridine and sodium hydroxide, stirring and mixing, reacting, after the reaction is completed, filtering, washing, and vacuum drying at 60° C. for 12 h to obtain modified hydroxyapatite; S2, ultrasonically dispersing nano-ferroferric oxide in anhydrous ethanol, adding γ-aminopropyltriethoxysilane after uniform dispersion, stirring and mixing, reacting, washing, and vacuum drying at 60° C. for 12 h to obtain aminoferroferric oxide; S3, mixing toluene, modified hydroxyapatite, aminated ferroferric oxide and triethylamine evenly, heating, reacting, after the reaction is completed, filtering, washing, and vacuum drying at 60° C. for 24 h to obtain modified ferroferric oxide-hydroxyapatite; S4. Evenly mix sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide and deionized water, add a crosslinking agent, an initiator and a catalyst in a nitrogen atmosphere, heat up, stir and mix to react, wash and freeze-dry after the reaction to obtain a dephosphorus polymer gel.

2. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The mass ratio of nano-hydroxyapatite, N,N-dimethylformamide, 2-butene-1-ylsuccinic anhydride, 4-dimethylaminopyridine and sodium hydroxide in S1 is 100:2500-3000:52-60:2-3:1-1.

5.

3. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The reaction temperature in S1 is 85-95° C., and the reaction time is 6-9 hours.

4. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The mass ratio of nano-ferroferric oxide, anhydrous ethanol and γ-aminopropyltriethoxysilane in S2 is 100:1800-2100:65-75.

5. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The reaction temperature in S2 is 25-35°C, and the reaction time is 2-4h.

6. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The mass ratio of toluene, modified hydroxyapatite, aminoferric oxide and triethylamine in S3 is 4500-6000:100:20-30:1-2.

7. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The reaction temperature in S3 is 80-90° C., and the reaction time is 12-14 h.

8. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The mass ratio of sodium alginate, modified ferroferric oxide-hydroxyapatite, N-(hydroxymethyl)acrylamide, acrylamide, deionized water, crosslinking agent, initiator and catalyst in S4 is 100:15-20:75-105:240-320:1200-1500:28-40:1-3:2-3.

5.

9. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: The reaction temperature in S4 is 55-65° C., and the reaction time is 5-8 h.

10. The method for preparing a phosphorus removal polymer gel according to claim 1, characterized in that: In the S4, the crosslinking agent is methylenebisacrylamide, the initiator is ammonium persulfate, and the catalyst is tetramethylethylenediamine.

Citation Information

Patent Citations

  • Method for preparaing dephosphorized and ferrum-carried activated carbon adsorbent

    CN102614854A

  • Preparation method of alginate-graphene compound double-network gel beads

    CN104785177A

  • Method for preparing magnesium-aluminum ion doped mesoporous TiO2 fluorine removal agent

    CN104707562A

  • SiO2 / C composite material for adsorbing heavy metal ions in water body and application thereof

    CN104941584A

  • Preparation method and application of pH response magnetic polystyrene-based porous microspheres

    CN110117380A

Cited By

  • Composite treatment agent for sewage treatment and preparation method thereof

    CN120039989A